Quantitative study of lyari waterways - Mansoor, Asif; Naeem, Rana Khalid; Mirza, Safia (2008)
Metropolitan city Karachi is the biggest and the most industrialized city of Pakistan which located at extreme west end of the Indus delta within the geographical coordinate between latitude 24 51 N 0 / and longitude 67 04 E 0 / . The Lyari river is one of the three rivers, along with the Malir and Hub rivers, which flows through the greater metropolitan area of the city. It is one of the major flood water-carrying river which passes through the main city area of Karachi. Its main tributaries are Gujar and Orangi nullahs. The entire untreated industrial and domestic sewerage water joins the river directly or through these nullahs. This river and adjacent developed area have been subjected to severe flooding on regular basis in the past. This flood causes loss of property and men adjoining to the river which is an enormous affair for legislative association. A large scale reconnaissance survey of the under study river has been conducted for compilation of data. The long term hydraulic characteristics of the river have been gauged for collecting sufficient data to determine frequent change. The L-Section and Cross-Section assessment of the river beds and its main tributaries has also been measured. The historic discharge from river catchments area has been collected from the time to time carried hydrologic studies. In this study field survey data has been utilized for quantification of the river. The model has been constructed for designing the open channel Lyari by using its existing position and measuring the peak discharge required. This model will enable to chanalize the storm river flow smoothly in future.